Pemberdayaan Masyarakat Desa Bukit Melintang Melalui Kukerta Bangun Kampung Di Desa Bukit Melintang Kabupaten Kampar - Hasnah Faizah; Clarence Jovita; Andra Owita Sari; Fadhlan Arifin; Gemilang Multani; Juwita Ovalina Putri; Miftahul Salsabila; Muhammad Riswan Azhari; Nabila Aisyah Bella; Simon Tanta Agral Silaban; Tomy Arianda Simanjuntak (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
Bukit Melintang is one of the villages that is the location of Riau University’s Bangun Kampung Community Service through Real Work Lectures (Kukerta) 2023. Kukerta is a form of community service program by lecturers and students. Through Kukerta, students with the guidance of field supervisors contribute by applying the knowledge and technology gained in college directly in the midst of rural communities. The service objectives of the Bukit Melintang Kukerta team are directed at community empowerment to improve the quality of human resources in developing the potentials in the village and providing solutions to existing problems in the village for the creation of a better Bukit Melintang village. The methods used start from observation, interviews, socialisation, and implementation of various work program designs. The results of the Kukerta Bangun Kampung service in Bukit Melintang describe the changes where the points of change of the target community are achieved through each work program that has been implemented in developing the potential and competence of the village community.